Desenvolvimento de um fotobiorreator automatizado de baixo custo para estudo de saturação de luz de microalgas. - Gabriel Bastos Braga (2018)
Despite its great potential, the use of microalgae for energy production purposes is not economically viable yet, due to their high production costs. One of the major bottlenecks for their large-scale production is the energy consumption for temperature control in photobioreactors used for their cultivation. The present work sought to understand the causes of overheating in photobioreactors, in order to outline strategies to reduce this overheating. Thus, microalgae light saturation curves were experimentally obtained for cultivation starting from three different initial concentrations. In cultures with low initial microalgae concentration, the light saturation can be observed directly, by simply evaluating the initial oxygen production rate. However, the effects of excess radiation are best observed when considering the biomass production over a longer period of growth, as inhibitory effects may be slow to manifest themselves in the rate of production. The biomass production rate is not affected initially, but excess illumination may impede continued growth in the long run. A good strategy to reduce heat dissipation costs in photobioractors for microalgae cultivation would be not only to avoid the incidence of infra-red and ultraviolet radiation, but to limit visible radiation with intensity above 1000 μmolphotons .m-2 .s-1. Another strategy to reduce overheating in photobioreactors may be to provide flashing light, alternating short intervals of light and dark. Such a measure improves the performance of microalgae production and reduces the demand for heat dissipation. This flashing was investigated here, but the use of higher frequencies, in order to maintain a production rate with large ranges and increasing energy efficiency, must still be evaluated. Executing this study required the development of an automated low cost photobioreactor. Equipped with a microcontroller, this reactor was able, through the implementation of a PID controller, to control the growth temperature regardless of external interferences and automatically capture and store online data of the sensors used to monitor the experimental microalgae growth, including the amount of heat dissipation. Through the use of the same microcontroller, it was also possible to adapt a low-cost turbidity sensor and calibrate it to measure turbidity continuously, with an accuracy comparable to that of commercial laboratory equipment, provided that it operates in one of two modes: either operating at constant temperature, or operating after carrying out a second calibration with at least 3 different temperatures within the expected range of operation.